A new species of myrmecophilous lady beetle in the genus Diomus (Coleoptera: Coccinellidae: Diomini) from Chiapas, Mexico that feeds on green coffee scale, Coccus viridis (Green) (Hemiptera: Coccidae) - Vandenberg, Natalia J.; Iverson, Aaron; Liere, Heidi (Zootaxa, 2018)
A new species of myrmecophilous lady beetle, Diomus lupusapudoves, sp. nov. (Coleoptera: Coccinellidae: Diomini), is described from a coffee agroecosystem in Chiapas, Mexico. The new species was found preying on the green coffee scale pest, Coccus viridis (Green), tended primarily by Azteca sericeasur Longino and Pheidole synanthropica Longino ants. The larval, pupal, and adult stages of the new species are described and habitus illustrations or photos provided along with anatomical details of the adult male and female genitalia. The species is most similar to Diomus thoracicus Fabricius         (=type species of Diomus), another myrmecophile, which inhabits ant nests and feeds on ant brood. The new species has a peculiar onisciform larva that lacks dorsal setae, features that it shares with D. thoracicus. The new species is only the second species in the genus reported as a myrmecophile, although the life histories of most species have been poorly documented.